Costing analysis of levofloxacin as antibiotic prophylaxis for pediatric household contacts of multi-drug resistant tuberculosis patients in a South African setting - Fortuin, Suereta (Department of Public Health and Family Medicine, 2021)
Background The incidence of TB in children under 15 years, accounts for 8% of the global TB burden. In 2018, the World Health Organisation (WHO) estimated that there were approximately 11 000 multi-drug resistant (MDR) TB cases in South Africa. Despite having very clear guidelines on TB treatment programs and management, availability of inexpensive diagnostic tests, curative and preventive therapies, and the widespread use of the BCG vaccines, South Africa continues to have the highest the number of MDR-TB cases per capita. Levofloxacin is used as part of the group of fluoroquinolones in the drug regimen recommended in the treatment of MDR-TB patients. In addition to investigating the clinical impact of levofloxacin as preventative antibiotic therapy, the expected costs of the intervention will be a critical input to determining feasibility and costs effectiveness, which will inform policy and implementation considerations. Methods We performed a cost analysis on using existing data from the Tuberculosis Child Multi-drug-resistant Preventative Therapy (TB-CHAMP) trial, conducted from a TB control program perspective. We used data from 510 childhood household contacts of MDR-TB patients in South Africa that were treated with levofloxacin for 6 months as a preventative therapy for MDR-TB. In our analysis we evaluated the estimated health system cost associated with provision of levofloxacin to childhood contacts of MDRTB patients in South Africa. Results The mean total cost of treating a child household contact, irrespective of their weight band is ZAR 5,289.79. When the cost were analysed by weight categories we found that the cost increased by weight category; ZAR 2,146.78 (under 5 kg), ZAR 4,714.58 (between 5-15.9 kg) and ZAR 6,606.67 (over 16 kg). We performed a comprehensive sensitivity analysis and found that the scheduled clinic visits were the major cost driver. Aside from the scheduled visits we observed that there was an increase in additional health service utilization for children with a weight more than 5kg. Conclusion We envisage that based on our analysis we will be able to inform policy decisions about the management and prevention of childhood household contacts of MDR-TB patients in developing TB themselves.